Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.13057/biodiv/d200221
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Variation in chemical constituent of Styrax sumatrana wood growing at different cultivation site in North Sumatra, Indonesia

Abstract: Iswanto AH, Siregar YS, Susilowati A, Darwis A, Hartono R, Wirjosentono B, Rachmat HH, Hidayat A, Fatriasari W. 2019. Variation in chemical constituent of Styrax sumatrana wood growing at different cultivation site in North Sumatra, Indonesia. Biodiversitas 20: 448-452. Kemenyan Toba (Styrax sumatrana) is known as endemic resin-producing trees that naturally grow in North Sumatra and distributed throughout five districts within the province. Different growing site may constitute to different characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In addition, the extractive content of the incense wood from North Tapanuli was also higher. Results from previous research conducted by Iswanto et al (2019) reported that the cellulose content and the extractive content of the incense wood from North Tapanuli were 25.94% and 39.87%, respectively, while those from Pakpak Bharat were 10.95 and 2.42% respectively. Cellulose is the main food source for termites.…”
Section: Mass Lossmentioning
confidence: 86%
See 4 more Smart Citations
“…In addition, the extractive content of the incense wood from North Tapanuli was also higher. Results from previous research conducted by Iswanto et al (2019) reported that the cellulose content and the extractive content of the incense wood from North Tapanuli were 25.94% and 39.87%, respectively, while those from Pakpak Bharat were 10.95 and 2.42% respectively. Cellulose is the main food source for termites.…”
Section: Mass Lossmentioning
confidence: 86%
“…Since habitat bio-physical conditions determine the morphological and physiological characteristics of the plants, an interesting phenomenon reported in a previous study by Rachmat et al (2017) showed that the S. sumatrana plants from North Tapanuli districts are very different compared with those from Pakpak Bharat District. A significant difference was also noted from the results of the chemical component analysis of the woods in varying growth sites in North Sumatra (Iswanto et al 2019).…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations